Chronic Pain in University Students: Biopsychosocial Factors and their Functional Impact - Mabe Castro, Diego; Mancilla Pardo, Pablo; Munzenmayer Morata, Matías; Cornejo Soto, Antonia Aracelli; Castillo-Aguilar, Matías; Mabe-Castro, Matías; Basualto-Alarcón, Carla; Nuñez-Espinosa, Cristian (My University, 2025)
Introduction. Non-cancer chronic pain is a significant global public health issue, particularly within specific populations, and is shaped by a complex interplay of biological, psychological, and social factors. University students face unique lifestyle challenges that may increase their vulnerability to chronic pain and its associated functional impairments. However, this population remains underrepresented in research, leaving important gaps in our understanding. Aim. This study explored the relationship between non-cancer chronic pain, its presence, characteristics, and functional impact, and biopsychosocial factors linked to university life, including physical activity, sleep quality, and mental health. Methods. A cross-sectional observational study was conducted among 157 full-time students from two universities in Chile's Austral Macrozone. Data were collected using online questionnaires assessing pain, sociodemographic information, sleep, chronotype, physical activity, and mental health. Statistical analyses were carried out using Bayesian modeling. Results. Females had a higher risk of chronic pain (exp(β) = 6.96), with greater intensity and functional impact. Engineering students were at higher risk compared to health sciences (exp(β) = 7.69), and health sciences compared to social sciences (exp(β) = 3.89). Moderate physical activity showed a protective effect against pain (exp(β) = 2.95). Matutine chronotypes and better sleep quality were linked to reduced functional impact and pain frequency. Conclusion. Biopsychosocial variables —including sociodemographic characteristics, physical activity levels, mental health, and sleep quality— were significantly associated with the presence, frequency, and functional consequences of chronic pain among Chilean university students. These findings highlight the importance of addressing such factors in the development of preventive and management strategies targeting chronic pain in this population.
Dolor crónico en estudiantes universitarios: factores biopsicosociales y su impacto funcional
Keywords: biopsychosocial model; chronic pain; health behavior; pain measurement; sex factors